Research Progress in Monitoring Technology of Cold Chain Logistics for Meat Products - Bin HAN; Dongmei LENG; Yuqian XU; Jianyang SHEN; Xin LI; Xiaochun ZHENG; Wei WANG; Dequan ZHANG; Chengli HOU (Shipin gongye ke-ji)
Cold chain logistics is an essential method for ensuring meat quality in China, which is a country that produces and consumes much meat. With the development of science and technology, and the gradual implementation of cold chain logistics planning policy, digitization, informatization, and visualization have become a focal point of development in cold chain logistics. However, temperature fluctuations will inevitably occur in the cold chain logistics process, particularly in long-distance transportation and extreme weather conditions to trigger the "chain breaks""pseudo-cold chains", and other issues, leading to a decrease in meat quality in the cold chain logistics process. Advanced technologies like big data, the internet of things, and artificial intelligence are becoming widely used as Industry 4.0 technology, which develops quickly. The combination of these technologies and various sensing devices, which are particularly effective in monitoring the cold chain of meat products, has become an effective way to resolve related issues. The focus of this article reviews the key progress of monitoring technology in the cold chain logistics of meat products, including information perception, information processing, and other essential aspects. To analyze the future development of meat cold chain logistics monitoring technology combined with sensors, narrowband internet of things, machine learning, and blockchain, and to provide theoretical support for the research and application of China's cold chain logistics monitoring technology.